2005
DOI: 10.1677/joe.1.06220
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status affects 20-hydroxyecdysone concentration and progression of oogenesis in Drosophila melanogaster

Abstract: Drosophila egg production depends upon the nutritional available to females. When food is in short supply, oogenesis is arrested and apoptosis of the nurse cells is induced at mid-oogenesis via a mechanism that is probably controlled by ecdysteroid hormone. We have shown that expression of some ecdysone-response genes is correlated with apoptosis of egg chambers. Moreover, ecdysteroid injection and application of juvenile hormone induces and suppresses the apoptosis, respectively. In this study, we investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
119
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(126 citation statements)
references
References 23 publications
5
119
1
1
Order By: Relevance
“…As previously shown, environmental stimuli, such as high temperature and nutritional shortage, induce up-regulation of 20E levels in adult flies (14,15). In this study, we have demonstrated that 20E levels are increased in male flies after they are paired with a mated female for 7 h, conditions under which a robust courtship LTM is generated.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…As previously shown, environmental stimuli, such as high temperature and nutritional shortage, induce up-regulation of 20E levels in adult flies (14,15). In this study, we have demonstrated that 20E levels are increased in male flies after they are paired with a mated female for 7 h, conditions under which a robust courtship LTM is generated.…”
Section: Discussionsupporting
confidence: 78%
“…Interestingly, 20E levels are significantly affected by environmental conditions, and changes in 20E levels influence the regulation of oogenesis. For example, high temperature and nutritional shortage result in an increase in the 20E titer (14,15), and induce apoptosis in oocytes, preventing oogenesis under these unfavorable conditions (15). It has also been reported that mutations that reduce the strength of ecdysone signaling in adults extend life span of Drosophila males and females by 40 to 50% (16), indicating the importance of the ecdysone hormonal pathway for adult physiology.…”
mentioning
confidence: 99%
“…Our study defined the dynamic expression pattern of Shd and EcR isoforms in late oogenesis and demonstrated the requirement of ecdysteroid signaling in ovulation. Ecdysteroids have also been shown to regulate early germ cell differentiation (35,36), egg chamber progression at stage 8-9 (29)(30)(31), and endocycle-to-gene-amplification switch at stage10B (33). This temporal action of ecdysteroids is reminiscent to their roles in regulating multiple larval and pupal transitions (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Ecdysteroids have long been known to play essential roles in developmental transitions, such as larval molting and metamorphosis (27,28). In contrast, the roles of ecdysteroids in adult physiology have just started to emerge (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39).…”
mentioning
confidence: 99%
“…For example, 20E concentrations in the ovaries and hemolymph rise when adult females are transferred onto a sugar diet without a yeast supplement. 9 This elevation of the 20E level apparently serves as a signal of nutritional shortage, leading to an arrest of oogenesis and the induction of apoptosis. As a result, females can use the limited energy and nutrients that are available for their own survival in exchange for reduced reproduction.…”
Section: The Steroid Molting Hormone and Stress Responses In Adult Fliesmentioning
confidence: 99%